Inhibitory effect of black tea (Camellia sinensis) theaflavins and thearubigins against HCT 116 colon cancer cells and HT 460 lung cancer cells - Imran, Ali; Butt, Masood Sadiq; Xiao, Hang; Imran, Muhammad; Rauf, Abdur; Mubarak, Mohammad S.; Ramadan, Mohamed Fawzy (Journal of food biochemistry, 2019)
Recently, phytochemical‐based dietary intervention has gained attention as a preventive and curative strategy against cancers owing to their safety, better tolerance, and economics. Against this background, black tea extract which contains the flavanol‐3‐ol, theaflavins (TF), and thearubigins (TR) with promising anti‐oncogenic activity were assessed to determine its in vitro inhibitory impact on colon cancer (HCT 116) and lung cancer cell lines (HT 460). In a dose‐dependent manner, results revealed that TF, TR, and their combinations cause inhibition in cell viability. However, TF imparted a maximum reduction in cell viability of HCT 116 and HT 460. Flow cytometry data revealed that TF, TR, and their combinations exhibited substantial cell arrest at the G2/M phase. The influence was more prominent in lung cancer cells (HT 460) when compared with colon cells (HCT 116). All treatments resulted in apoptosis, however, the combination of TF and TR exhibited the highest apoptotic ability in comparison to individual treatments. TF and TR exhibited a synergistic impact and significantly inhibited cell proliferation of HCT 116 and HT 460 in dose‐ and time‐dependent manners by inducing apoptosis and cell cycle arrest, wherein TF showed a more pronounced impact. Practical applications Results from the present study revealed that black tea‐isolated polyphenols (TF and TR) exhibited a significant inhibition of lung and colon cancer cell growth. A promising synergistic effect of TF and TR as inhibitors of cancer cells was observed. More clinical work, perhaps on a human subject, is needed before these two isolated compounds can be prescribed as anticancer drugs.